SYSTEM-ACTIVITY TEACHING APPROACH in UKRAINIAN HIGHER EDUCATION INSTITUTIONS - Samoilenko, Elena; Davidov, Pavel; Avetisova, Irina; Potsulko, Elena; Shundel, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the essential characteristics and specifics of teaching in higher education through a system-active approach. The introduction includes a retrospective of the emergence of the concept of «system-activity approach», the prerequisites for its formation. The work tracks modern trends in the educational system of Ukraine, which necessitate the use of effective teaching methods to form a highly effective teaching structure. The article also includes an overview of the methodological base of the system-activity approach and consideration of the main principles and techniques used in its implementation.